2022
DOI: 10.1159/000525248
|View full text |Cite
|
Sign up to set email alerts
|

Physical Distancing and Mental Well-Being in Youth Population of Portugal and Brazil during the COVID-19 Pandemic

Abstract: <b><i>Background:</i></b> The COVID-19 pandemic may affect youth’s physical and mental well-being, partially because of the countries’ rules to contain the virus from spreading. However, there is still uncertainty about the impact of physical distancing on youth’s mental health. We aimed to estimate the prevalence of feeling agitated, anxious, down, sad, or low mood (FNF) due to physical distance measures and verify which factors are associated with young Portuguese and Brazilian people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…This study also obtains results consistent with other studies, where the closure of schools (not necessarily synonymous with protection), physical and mental well-being and government decisions are key to the safety of children and young people [30][31][32][33]. We must not also forget two key points in LAC; the higher poverty has induced a faster spread of the virus [34], and the current scenario where the omicron variant has triggered infections in all age groups almost without control; fortunately, deaths have not skyrocketed to the same extent.…”
Section: Trinidad and Tobagosupporting
confidence: 91%
“…This study also obtains results consistent with other studies, where the closure of schools (not necessarily synonymous with protection), physical and mental well-being and government decisions are key to the safety of children and young people [30][31][32][33]. We must not also forget two key points in LAC; the higher poverty has induced a faster spread of the virus [34], and the current scenario where the omicron variant has triggered infections in all age groups almost without control; fortunately, deaths have not skyrocketed to the same extent.…”
Section: Trinidad and Tobagosupporting
confidence: 91%
“…Some studies have reported that school restrictions do more harm than good and that they were executed in an empirical context 39,40,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…This was higher among women, immigrants older than 45 years, with lower levels of education and lower incomes (Gama et al, 2022). The confinement and physical distance due to COVID-19 increased the mental health problems of both Portuguese (36%) and Brazilian (52%) citizens, despite few studies focusing on the topic during this critical period (Gil et al, 2022). Furthermore, understanding the impact of mental health care on the Portuguese population is still limited, and data are scarce, especially those exploring the social determinants of health, such as their social networks and social capital.…”
Section: Migration In Portugal: Health Challenges and The Burden Of C...mentioning
confidence: 99%